Featured Article: Psychosocial and Family Functioning Among Latino Youth With Spina Bifida. (17th July 2017) - Papadakis, Jaclyn Lennon; Acevedo, Laura; Ramirez, Sonia; Stern, Alexa; Driscoll, Colleen F; Holmbeck, Grayson N
Abstract: Objective: This study examined differences in psychosocial and family functioning between Latino and non-Latino Caucasian youth with spina bifida (SB), and examined family functioning as a predictor of youth psychosocial functioning as moderated by ethnicity. Methods: Participants were part of a larger, longitudinal study (Devine, Holbein, Psihogios, Amaro, & Holmbeck, 2012 ) and included 74 non-Latino Caucasian youth with SB and 39 Latino youth with SB ( M age = 11.53, 52.2% female). Data were collected at Time 1 and 2 years later, and included questionnaire and observational data of psychosocial and family functioning. Results: Latino youth demonstrated fewer externalizing symptoms, less family conflict, but also less social competence. Family conflict was associated with psychosocial functioning in Latino youth, while family cohesion, conflict, and stress were associated with psychosocial functioning in non-Latino Caucasian youth. Conclusions: Psychosocial and family functioning, and their relationship over time, may be different in Latino versus Caucasian youth with SB.